(untitled) (Journal of Health Sciences, 2020)
Introduction: Lumbar puncture is a procedure frequently used in anesthetic practice. For the success of the procedure, prediction of skin to subarachnoid space distance (SSD) is valuable. In this study, we aimed to evaluate the relationship between SSD with age and body mass index (BMI). Methods: Two hundred and fifty patients, ASA physical status I, II, and III scheduled to undergo elective surgery under spinal anesthesia, were studied. Spinal anesthesia was induced in the sitting position at the L3–4 vertebral level using a midline approach. Furthermore, the level of L3–L4 was identified by palpation, using Tuffier’s line as a guide. Following an intrathecal injection, the spinal needle was grasped between the thumb and the index finger during its removal from the patient’s back. From the grasping point, SSD was measured using rulers. Results: Mean values of SSD at the L3-4 interspace were 55.43±6.47 mm (range 35-74). Statistically significant correlations were observed between SSD with BMI and body weight (ρ=0.650, P<0.001 and ρ=0.651, P<0.001, respectively). Statistically significant correlation was not found between SSD with age, gender and body height (ρ=0.120, P=0.058; ρ=-0.047, P=0.4568 and ρ=0.089, P=0.159, respectively). Conclusions: SSD is affected by BMI and body weight but not by age, gender and body height.